POLYPLOID PRODUCTION IN LILIUM LEICHTLINII VAR. MAXIMOWICZII USING COLCHICINE - Jae-Yun Heo; Seong-Ho Jeong; Han-Ryul Choi; Sung-Min Park (Journal of Animal and Plant Sciences, 2016)
This study was carried out to assemble the basic data on the breeding of new L. leichtlinii var. maximowiczii cultivars. Various concentrations and soaking times were investigated to determine the most effective approach to induce polyploid plants via colchicine treatment. In determining the survival rate and root formation degree of bulblets by colchicine treatment, it was found that the higher the colchicine concentration and the longer the soaking time were, the more the survival rate and root formation degree decreased. Chromosome analysis by flow cytometry and chromosome counting revealed that colchicine treatment produced a total of 83 polyploid plants. Although the soaking treatment in 0.2% colchicine for 9 hours induced the highest percentage of polyploid plants among the survived plants, a high percentage of the plants died. Interestingly, soaking treatment in 0.05% colchicine for 9 hours induced 15 polyploid plants, which was about 50% of the total number of bulblets tested in this study, hence this was considered the most suitable treatment to produce polyploid in L. leichtlinii var. maximowiczii.
Keywords: L. leichtlinii var. maximowiczii; polyploidy; flow cytometry; chromosome counting; colchicines